Cross-cultural differences in early caregiving: levels of mind-mindedness and instruction in UK and India - Bozicevic, Laura; Hill, Jonathan; Chandra, Prabha S.; Omirou, Agni; Holla, Chaithra; Wright, Nicola; Sharp, Helen (Frontiers in Child and Adolescent Psychiatry, 2023)
Most studies on parenting and its role in child development are conducted in Western countries, but it cannot be assumed that characteristics of parental practices are similar in non-Western settings. Research characterizing cultural differences in parenting is required to inform the focus of studies designed to test differential outcomes from such practices in children over time and across cultures. The present cross-cultural study examined differences in maternal speech during mother-child interactions, and, specifically, in the use of mind-mindedness, instruction and control, and the expression of warmth (i.e., positive comments). We observed 100 dyads (50 from the UK and 50 from India) during mother-infant play interactions at 7 months. Maternal speech was transcribed and translated prior to independent coding, and this was coded using established measures together with a newly developed measure of ‘Instructions’. Substantially large differences between UK and Indian mothers were observed. Compared with UK mothers, Indian mothers made fewer mind-minded comments about their infants, and they issued more instructions and made more controlling and positive comments. Findings from this study might reflect cultural differences in how parental style might be expressed according to cultural priorities and values. The implications of these very large differences in parenting across cultures for child development remain to be investigated and are discussed in the present paper.